The 6-year trajectory of non-traumatic knee symptoms (including patellofemoral pain) in adolescents and young adults in general practice: a study of clinical predictors. Issue 6 (27th November 2014) - Kastelein, M; Luijsterburg, P A J; Heintjes, E M; van Middelkoop, M; Verhaar, J A N; Koes, B W; Bierma-Zeinstra, S M A
Abstract : Aims: (1) To assess the 1-year and 6-year courses of non-traumatic knee symptoms in adolescents and young adults presenting in general practice. (2) To identify prognostic factors for persistent knee symptoms at 1-year follow-up. Methods: Adolescents and young adults (12–35 years; n=172) with non-traumatic knee symptoms were included in the cohort study by their general practitioner (GP) and followed for 6 years. Multivariable logistic regression analysis was used to identify prognostic factors for persistent knee symptoms at 1-year follow-up and the area under the receiver operating curve (AUC) was calculated. Results: Persistent knee symptoms in patients receiving a GP diagnosis of unspecified knee symptoms were reported by 41% of the patients at 1-year follow-up and by 19% of the available patients at 6-year follow-up. Patients receiving a GP diagnosis of patellofemoral pain syndrome had the worse prognosis, with 40% reporting persistent knee symptoms at 6-year follow-up. Prognostic factors associated with persistent knee symptoms at 1-year follow-up were BMI >25, low/middle education level, bilateral symptoms and self-reported absence of crepitus of the knee (AUC 0.80) for patients receiving a GP diagnosis of unspecified knee symptoms. For patients receiving a GP diagnosis of patellofemoral pain syndrome, prognostic factors were low/middle education level, poor health, having bilateral symptoms and self-report of a swollen knee (AUC 0.76). Conclusions: The prognosis of non-traumatic knee symptoms in adolescents and young adults in general practice is not as good as was previously assumed. Several prognostic factors collected at baseline were associated with persistent knee symptoms at follow-up. However, the results should be replicated in another larger study.